Improved moth flame optimization algorithm to optimize cost-oriented two-sided assembly line balancing - M. F. F., Ab Rashid; A. N. M., Rose; N. M. Zuki, N. M.; F. R. M., Romlay (Emerald Group Publishing Ltd., 2019)
This paper aims to propose an improved Moth Flame Optimization (I-MFO) algorithm to optimize the cost-oriented two-sided assembly line balancing (2S-ALB). Prior to the decision to assemble a new product, the manufacturer will carefully study and optimize the related cost to set up and run the assembly line. For the first time in ALB, the power cost is modeled together with the equipment, set up and labor costs.